Speciation of fast and slow biochemical oxygen demand - Zainudin, Zaki; Abdul Rahman, Norazah; Abdullah, Norizan (IIUM Press, 2011)
Biochemical Oxygen Demand (BOD) is a critical constituent used to measure the strength of organic pollution in water. Although new methodologies for organic quantification such as the Chemical Oxygen Demand (COD), Total Organic Carbon (TOC) tests and respirometry methodology have been introduced, the BOD method for determining organic strength is still preferred by the environmental community, despite its sometimes random and arbitrary results. The BOD test procedure dates back to early part of the 20th century by measuring dissolved oxygen (DO) depletion within a five-day period at a designated incubation temperature (Zainudin, 2008). The DO depletion is attributed to oxygen consumption (BOD) by microbial organisms present in the water column during the stabilization of biodegradable organic matter. This aspect of including the microbial population in the test is a feature not addressed in other modern methods for organic quantification (save perhaps respirometry) and is of significant importance for ambient water quality preservation proceedings, such as in the use of water quality models.